Optimization of parameters and regimes for excavator with replaceable milling head - Prystailo, Arsen; Yeremenko, Mykhailo; Hereha, Yurii (КНУБА, 2025)
The issue of increasing the efficiency of the single-bucket excavator with the replaceable milling head during earthworks in transport construction are considers in the paper. The optimal parameters and operating modes depending on the soil strength are substantiated based on the analysis of technological schemes and graph-analytical dependencies. The proposed approaches provide the increase in performance by 12–18% and the reduction in specific energy consumption by up to 15%.
Keywords: excavator; milling head; parameter; operating mode; performance; optimization; earthworks